2018
DOI: 10.1038/s41467-018-03111-4
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal calcium binding of α-synuclein modulates synaptic vesicle interaction

Abstract: Alpha-synuclein is known to bind to small unilamellar vesicles (SUVs) via its N terminus, which forms an amphipathic alpha-helix upon membrane interaction. Here we show that calcium binds to the C terminus of alpha-synuclein, therewith increasing its lipid-binding capacity. Using CEST-NMR, we reveal that alpha-synuclein interacts with isolated synaptic vesicles with two regions, the N terminus, already known from studies on SUVs, and additionally via its C terminus, which is regulated by the binding of calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
249
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(304 citation statements)
references
References 76 publications
23
249
2
Order By: Relevance
“…Of all essential metal ions that AS encounters in vivo , the specific interactions of Cu ions with His50 and the N‐terminal group are the most physiologically relevant, given the high affinity for copper at these anchoring sites. Finally, more recent evidence supports an important role for AS in calcium‐dependent vesicular trafficking, associated to AS‐Ca(II) interactions (Lautenschläger et al ). Hence, in the following sections detailed discussions of the interactions of this protein with calcium and copper ions are presented.…”
Section: α‐Synuclein Is a Metal‐binding Proteinmentioning
confidence: 87%
See 3 more Smart Citations
“…Of all essential metal ions that AS encounters in vivo , the specific interactions of Cu ions with His50 and the N‐terminal group are the most physiologically relevant, given the high affinity for copper at these anchoring sites. Finally, more recent evidence supports an important role for AS in calcium‐dependent vesicular trafficking, associated to AS‐Ca(II) interactions (Lautenschläger et al ). Hence, in the following sections detailed discussions of the interactions of this protein with calcium and copper ions are presented.…”
Section: α‐Synuclein Is a Metal‐binding Proteinmentioning
confidence: 87%
“…On the other hand, using a microdialysis technique it was proposed that AS binds Ca(II) at the C‐terminal region with a K D = 2–300 μM (Nielsen et al ). However, recent NMR and mass spectrometry results suggest that it can bind up to 6‐8 calcium ions with a K D in the range 21 μM (Lautenschläger et al ). This dissociation constant lies well within the range of physiological pre‐synaptic calcium fluctuations, reaching up to hundreds of micromolar in healthy neurons upon neuronal stimulation.…”
Section: α‐Synuclein Is a Metal‐binding Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with a weak interaction, the protein localizes relatively late to developing synapses in cultured neurons (Withers et al 1997). In vitro, a-synuclein can associate with synaptic vesicles (Nakamura et al 2008) and Ca ++ has been suggested to regulate the interaction (Lautenschlager et al 2018). To understand how a-synuclein localizes to pre-synaptic boutons, we previously used fluorescence recovery after photobleaching (FRAP).…”
Section: Pre-synaptic Location Of A-synucleinmentioning
confidence: 99%